Designing a Website-Based Cooperative Application - Paul Ferdinand, Jean; Juli Christanto, Henoch; Olivia Sereati, Catherine (Jurnal Elektro, 2023)
The development of the times in the field of technology allows information to be obtained quickly and easily. We often encounter exchange of information in the world of work, one of the business entities that is very dependent on the exchange of information is cooperatives. In traditional cooperatives, the use of services requires users to come directly to the physical location of the cooperative. The process of recording user data and transaction history is also still done manually, namely by writing it on a book, so it takes a long time. The cooperative system created is a web-based application with the Laravel framework and cooperative data managed using MySQL. Designing a web-based application will provide easy access to cooperative services and decrease the time required for transaction processing for users and increase the efficiency of cooperative management for cooperative managers.